Fuzzy Estimation of the Character of the Securities Market - G. Y. Ratushnyak; A. G. Sukhanova (Vestnik MGIMO-Universiteta)
To make the right decisions regarding the purchase or sale of financial assets the definition of the nature of the securities market is required. Existing methods of evaluation of the state securities market does not fully take into account the probability distribution of the states and fuzzy-multiple description of the character of securities market. For the efficient operation of the securities market new methods of analysis and forecasting of its state are required. In this paper we propose a fuzzy-multiple algorithm to evaluate the character of the securities market. This algorithm contains the operations of fuzzy sets theory. The fuzzy of the character of the securities market manifests itself in the «blur» of the boundaries of its varieties. The expert system of a fuzzy conclusion is developed for an estimation of the character of the securities market. In this article the expert system of fuzzy inference was developed for a fuzzy assessment of the character of the securities market. As instrumental development environment a system of computer mathematics Mathcad was used. For the characteristics of the market RTS Index was used. Developed expert system allows to enter specific values of the input indicators to obtain an estimate of the character of the securities market. The use of this expert system allows system users to resolve uncertainty when making decisions, to navigate the situation on the securities market and make the right decisions regarding the purchase or sale of financial assets. Developed in the work of the expert system was applied for the case volatility market.